New ICT in the Peruvian Andes: Theoretical Foundation and Bibliographical Balance - Sánchez-Dávila, Mario (2016)
On the one hand, this paper explains the theoretical foundations on which this proposal for digital anthropology in the Peruvian Andes is based (on the origins of digital anthropology, discussions on oral and written technology, and theories of digital technology as social practice). And, on the other hand, this paper presents a bibliographical balance of the studies on the new ICT in the Peruvian Andes (on identity expression, productive development and formal education in the Andean world).